Metabolism of the vacuolar pathogen Legionella and implications for virulence - Manske, Christian; Hilbi, Hubert (Frontiers in Cellular and Infection Microbiology, 2014)
Legionella pneumophila is a ubiquitous environmental bacterium that thrives in fresh water habitats, either as planktonic form or as part of biofilms. The bacteria also grow intracellularly in free-living protozoa as well as in mammalian alveolar macrophages, thus triggering a potentially fatal pneumonia called “Legionnaires’ disease”. To establish its intracellular niche termed the “Legionella-containing vacuole” (LCV), L. pneumophila employs a type IV secretion system and translocates 300 different “effector” proteins into host cells. The pathogen switches between two distinct forms to grow in its extra- or intracellular niches: transmissive bacteria are virulent for phagocytes, and replicative bacteria multiply within their hosts. The switch between these forms is regulated by different metabolic cues that signal conditions favorable for replication or transmission, respectively, causing a tight link between metabolism and virulence of the bacteria. Amino acids represent the prime carbon and energy source of extra- or intracellularly growing L. pneumophila. Yet, the genome sequences of several Legionella spp. as well as transcriptome and proteome data and metabolism studies indicate that the bacteria possess broad catabolic capacities and also utilize carbohydrates such as glucose. Accordingly, L. pneumophila mutant strains lacking catabolic genes show intracellular growth defects, and thus, intracellular metabolism and virulence of the pathogen are intimately connected. In this review we will summarize recent findings on the extra- and intracellular metabolism of L. pneumophila using genetic, biochemical and cellular microbial approaches. Recent progress in this field sheds light on the complex interplay between metabolism, differentiation and virulence of the pathogen.